التفاعل المصطلحي بين أصول النحو وأصول الفقه – بين استنساخ التجربة وخصوصيَّة التَّناول - حذيق, العيد (University of Eloued جامعة الوادي, 2021)
هذا البحثُ بعنوان: التَّفاعلُ المُصطلحيُّ بين علمي أصول النَّحو وأصول الفقه - بينَ استنساخِ التَّجربة وخُصوصيَّة التَّناول -؛ وهو دراسةٌ في إشكاليَّة التَّأثُّر والتَّأثير بين علمي أصول النَحو وأُصول الفقه، في جانبٍ من جوانب العلاقة بينهما، هو جانبُ المُصطلحات، ومحاولة تلمُّسِ مدى أصالة المُصطلحات في أصول النَّحو على وجه الخُصوص. ولِمُعالجة هذا الإشكال؛ سلكت الخُطَّة الآتية: مقدِّمةً ومقصدين وخاتمةً. تناولت المقدمة التعريف بمصطلحات البحث الرئيسة، فيما كان المقصدُ الأولُ نظرةً في تاريخ العلاقة بين علوم اللغة وعلوم الشرع، وعالج المقصد الثاني أثر أصول الفقه في مصطلحات أصول النحو، وتكفَّلت الخاتمة بتسجيل النتائج المُتوصَّل إليها. هذا وإنَّ من أهمِّ ما توصَّلْتُ إليهِ من نتائجَ: أنَّ لعلمِ أصول الفقه أثرًا كبيرًا في بلورةِ مصطلحات أصول النحو، باعتراف النُّحاة أنفسهم، وأنَّ هذا الأثرَ على كبره من جهة الشَّكل؛ فإنَّه لم يُلْغِ خُصوصيَّة التَّناول من جهة المضمون. Abstract This paper entitled "The Terminological Interaction Between the Science of Grammatical Origins and the Principles of Islamic jurisprudence- Between the Reproduction of the Experience and the Particularity of the Treatment", studies the influence (influence and being influenced) each of the science of grammatical origins and the principles of Islamic jurisprudence has on the other in the terminology aspect of their relationship. To address the issue in hand, I devised a plan of an introduction, two chapters and a conclusion. The introduction deals with defining the research's main terms, the first chapter provides a historical background to the relationship between linguistics and Sharia Sciences; and the second chapter tackles the influence of the principles of jurisprudence on the terminology of the science of grammatical origins. The conclusion contains the findings of the research which include : o The principles of Islamic jurisprudence has a great influence on the formulation of the terminology of the science of grammatical origins , by the acknowledgements of the grammarians themselves and ; o This influence, with its magnitude in terms of form, did not eliminate the particularity of treatment in terms of content.
The Terminological Interaction Between the Science of Grammatical Origins and the Principles of Islamic jurisprudence- Between the Reproduction of the Experience and the Particularity of the Treatment
مداخلة بملتقى المصطلح النَّحويُّ بين الهجر والاستعمال كلية الآداب واللغات. جامعة أبوبكر بلقايد تلمسان 31 مارس 2021
Keywords: أصول النَّحو، أصول الفقه، العلوم الشَّرعية، علوم اللغة العربيَّة، التفاعل; Principles of grammar. Fundamentals of jurisprudence. Sharia Sciences. Arabic Language Sciences. Interaction